Potent Pyrimidine and Pyrrolopyrimidine Inhibitors of Testis‐Specific Serine/Threonine Kinase 2 (TSSK2). (20th October 2017) - Hawkinson, Jon E.; Sinville, Rondedrick; Mudaliar, Deepti; Shetty, Jagathpala; Ward, Timothy; Herr, John C.; Georg, Gunda I.
Abstract: Testis‐specific serine/threonine kinase 2 (TSSK2) is an important target for reversible male contraception. A high‐throughput screen of ≈17 000 compounds using a mobility shift assay identified two potent series of inhibitors having a pyrrolopyrimidine or pyrimidine core. The pyrrolopyrimidine10 (IC50 22 nm ; GSK2163632A) and the pyrimidine17 (IC50 31 nm ; ALK inhibitor 1) are the most potent TSSK2 inhibitors in these series, which contain the first sub‐100 nanomolar inhibitors of any TSSK isoform reported, except for the broad kinase inhibitor staurosporine. The novel, potent pyrimidine TSSK2 inhibitor compound19 (IC50 66 nm ; 2‐[[5‐chloro‐2‐[2‐methoxy‐4‐(1‐methylpiperidin‐4‐yl)anilino]pyrimidin‐4‐yl]amino]‐ N ‐methylbenzenesulfonamide) lacks the potential for metabolic activation. Compound19 had a potency rank order of TSSK1>TSSK2>TSSK3>TSSK6, indicating that potent dual inhibitors of TSSK1/2 can be identified, which may be required for a complete contraceptive effect. The future availability of a TSSK2 crystal structure will facilitate structure‐based discovery of selective TSSK inhibitors from these pyrrolopyrimidine and pyrimidine scaffolds. Abstract : Sperm beware ! Testis‐specific serine/threonine kinase 2 (TSSK2) plays an important role in spermiogenesis and fertilization. A robust mobility shift assay high‐throughput screen identified a pyrrolopyrimidine and a pyrimidine series of TSSK2 ATP site inhibitors. A pyrimidine analogue lacking metabolic liability was identified as a potent dual inhibitor of TSSK2 and TSSK1, demonstrating the potential to identify inhibitors of multiple TSSKs for male contraception.